An architecture for QoS-enabled video telephony in a 3GPP 4G evolved packet core environment - Belqasmi, Fatna; Alipour, Hanieh; Ferjani, Malek El; Glitho, Roch H. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Video telephony is the real time exchange of voice and video between end-users, and is the basis of a wide range of applications. Quality of service (QoS) enables a level of network performance control which makes it possible to meet specific applications and/or end-user requirements. This paper proposes an architecture for QoS-enabled video telephony in a 3GPP 4G Evolved Packet Core (EPC) environment. The architecture uses EPC as enabler to provide a refined differentiated QoS scheme that does not exist in the state of the art. The scheme allows prioritization between different sessions of the same video telephony application running in the same network. End-users can therefore use one application for different purposes (e.g. for business video calls and for private video calls) by assigning the appropriate priorities. We have built a proof of concept prototype using the Fraunhofer Fokus OpenEPC as the 3GPP 4G EPC infrastructure and have made some preliminary performance measurements. The architecture and the operational procedures are presented, along with the prototype and the performance measurements. Related work is also reviewed.